A first approach to human biometeorology research in Brazil: a systematic review and meta-analysis - Krüger, Eduardo L.; Gobo, João Paulo Assis; Nedel, Anderson Spohr; Gonçalves, Fabio Luiz Teixeira; Lucio, Paulo Sérgio; Tejas, Graziela Tosini; Piacenti-Silva, Marina [UNESP] (Springer Nature, 2022)
This systematic review aims to give an overview of the diversity of research areas related to human biometeorology in Brazil. The main focus of this paper addresses research trends, represented by published papers with national and international authorship, main contributions and shortcomings, as well as challenges and prospects of research in this area of study. An extensive literature search was conducted in the Scopus, Web of Science, and Science Direct databases so as to identify relevant publication output up to July 2021 related to the research area. The screening resulted in 96 studies chosen for full-text reading. Overall, results indicated a reduced amount of articles on the subject matter published internationally, with noticeable gaps in research in some regions of the country, such as the Amazon region and in the Brazilian Midwest region. Research gaps in relevant areas have been identified with limited output in the climate dimensions of tourism, vector-borne diseases, mortality and morbidity in urban centers. Such gaps should further encourage researchers to engage in research focused on those areas.
Keywords: Bioclimate; Brazil; Chi-squared test; Contingency table; Correspondence analysis; Disease; Human biometeorology; Thermal comfort